Empirical comparison of personal agency development in students of vocational training programmes in the academic and practical training conditions - Igor B. Akimov; Alexander V. Kaptsov; Viktor I. Panov; Irina А. Ivkina (Saratov State University, 2022)
Practical training of students in the system of secondary vocational education (SVE) is the most important condition for the development of their ability to be the subjects of the future profession and, accordingly, masters of their craft. The personal agency development is considered within the framework of an eco-psychological approach. The objective of the study is to compare the impact of academic and practical training on the students' personal agency development in vocational training programmes. The research hypothesizes that practical training of students contributes to the development of cognitive and regulatory abilities to a greater extent than academic training. This, in turn, increases the effectiveness of the students' personal agency development stages in their mastering of the professional activity. The study was conducted on a sample of two experimental and two control students' groups (N = 77, 3 rd-year students of technical orientation, M = 18.4, Sd = 0.8) by means of the diagnostic techniques: the questionnaire on the personal agency development stages ОСС-С4 (A.V. Kaptsov, E. I. Kolesnikova, V. I. Panov), the questionnaire on methods of performing educational actions ОСС-СФ3 (A. V. Kaptsov, E. I. Kolesnikova), the questionnaire on the style of behavior self-regulation ССП-М (V. I. Morosanova) and the methodology of life-meaning orientations СЖО (D. A. Leontiev). It has been revealed that during the academic training, ratios of manifestation of students' personal agency development stages in secondary vocational education have no statistically significant differences. It has been found out that practical training and academic training have different predictors of the personal agency development stages that depend on the specialty the students are majoring in. The research shows that in the conditions of practical training the students' groups are divided into two unequal informal micro groups depending on the predominance of their eco-psychological subject-joint interaction type. Moreover, the success of the development of the "Student" stage has predictors in the form of the stage manifestation ratio, and manifestation of the conscious self-regulation components and life meaning orientations. The significance of the results obtained lies in the positive impact of practical training on the personal agency development in students of vocational training programmes.